Photoperiodic induction without light-mediated circadian entrainment in a High Arctic resident bird - Appenroth, Daniel; Melum, Vebjørn Jacobsen; West, Alexander Christopher; Dardente, Hugues; Hazlerigg, David; Wagner, Gabriela (Journal of Experimental Biology, 2020)
Organisms use changes in photoperiod to anticipate and exploit favourable conditions in a seasonal environment. While species living at temperate latitudes receive day length information as a year-round input, species living in the Arctic may spend as much as two-thirds of the year without experiencing dawn or dusk. This suggests that specialised mechanisms may be required to maintain seasonal synchrony in polar regions. Svalbard ptarmigan ( Lagopus muta hyperborea ) are resident at 74–81°N latitude. They spend winter in constant darkness (DD) and summer in constant light (LL); extreme photoperiodic conditions under which they do not display overt circadian rhythms. Here, we explored how Arctic adaptation in circadian biology affects photoperiodic time measurement in captive Svalbard ptarmigan. For this purpose, DD-adapted birds, showing no circadian behaviour, either remained in prolonged DD, were transferred into a simulated natural photoperiod (SNP) or were transferred directly into LL. Birds transferred from DD to LL exhibited a strong photoperiodic response in terms of activation of the hypothalamic thyrotropin-mediated photoperiodic response pathway. This was assayed through expression of the Eya3 , Tshβ and deiodinase genes, as well as gonadal development. While transfer to SNP established synchronous diurnal activity patterns, activity in birds transferred from DD to LL showed no evidence of circadian rhythmicity. These data show that the Svalbard ptarmigan does not require circadian entrainment to develop a photoperiodic response involving conserved molecular elements found in temperate species. Further studies are required to define how exactly Arctic adaptation modifies seasonal timer mechanisms.